Harris & Harris' the radiology of emergency medicine - Harris, John; Pope, Thomas Lee (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
"Edited by a renowned musculoskeletal radiologist and an internationally recognized Emergency Radiologist, and enhanced by contributions from invited acknowledged authorities, the Fifth Edition of this comprehensive reference is unsurpassed as a source of practical information on imaging of the acutely ill and injured patient during the acute phase of their emergent admission. Ideal for both the radiologist and for all members of the emergency team, the text builds upon current applications of plain-film radiography--while adding substantial coverage of other modalities, including MPCT and MRI. The fifth edition has again strived to keep up with the changing technology in diagnostic imaging in addition to emphasizing current practice in EDs and trauma centers. New chapters on imaging of skull fractures, maxillofacial trauma, chest trauma, and the acetabulum have been added to this volume to emphasize the importance of these areas with respect to imaging techniques and changes in clinical diagnosis and practice. In addition to redefining the importance of standard radiographs, the fifth edition has incorporated high-quality multidetector computed tomographic (CT) images, 3-D reformations, and magnetic resonance imaging to provide new information with evolving clinical practice"--Provided by publisher